HTTP developer's handbook - Shiflett, Chris (Developer's library., 2003)
HTTP is the protocol that powers the Web. As Web applications become more sophisticated, and as emerging technologies continue to rely heavily on HTTP, understanding this protocol is becoming more and more essential for professional Web developers. By learning HTTP protocol, Web developers gain a deeper understanding of the Web's architecture and can create even better Web applications that are more reliable, faster, and more secure. The HTTP Developer's Handbook is written specifically for Web developers. It begins by introducing the protocol and explaining it in a straightforward manner. It then illustrates how to leverage this information to improve applications. Extensive information and examples are given covering a wide variety of issues, such as state and session management, caching, SSL, software architecture, and application security.